2018
DOI: 10.3389/fpls.2018.00645
|View full text |Cite
|
Sign up to set email alerts
|

Starch Synthase IIa-Deficient Mutant Rice Line Produces Endosperm Starch With Lower Gelatinization Temperature Than Japonica Rice Cultivars

Abstract: The gelatinization temperature of endosperm starch in most japonica rice cultivars is significantly lower than that in most indica rice cultivars. This is because three single nucleotide polymorphisms in the Starch synthase (SS) IIa gene in japonica rice cultivars (SSIIaJ) significantly reduce SSIIa activity, resulting in an increase in amylopectin short chains with degree of polymerization (DP) ≤ 12 compared to indica rice cultivars (SSIIaI). SSIIa forms a trimeric complex with SSI and starch branching enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(113 citation statements)
references
References 40 publications
18
92
0
Order By: Relevance
“…The 8% reduction observed in the total starch content of the shrunken lines and the slight reduction in peak gelatinization temperature (at least 2 • C) of all shrunken and opaque lines tested also support the hypothesis that the residual SSIIa in Nipponbare has functional roles because its downregulation leads to significantly altered starch biosynthesis in the rice grain. The reduction of the peak gelatinization temperature was consistent with the earlier report by Miura et al (2018), which observed a reduction of about 6 • C in the gelatinization temperature of the null SSIIa line.…”
Section: Effect Of Downregulating Ssiia On Starch Granule Structure Asupporting
confidence: 92%
See 4 more Smart Citations
“…The 8% reduction observed in the total starch content of the shrunken lines and the slight reduction in peak gelatinization temperature (at least 2 • C) of all shrunken and opaque lines tested also support the hypothesis that the residual SSIIa in Nipponbare has functional roles because its downregulation leads to significantly altered starch biosynthesis in the rice grain. The reduction of the peak gelatinization temperature was consistent with the earlier report by Miura et al (2018), which observed a reduction of about 6 • C in the gelatinization temperature of the null SSIIa line.…”
Section: Effect Of Downregulating Ssiia On Starch Granule Structure Asupporting
confidence: 92%
“…In this study, the already low expression of weakly active japonica-type SSIIa in Nipponbare endosperm was further downregulated to determine any impact on its possible roles in amylopectin biosynthesis and starch structure. Our results, using a different japonica rice line (Nipponbare) and a different technique (RNA silencing), are in broad agreement with the results obtained by Miura et al (2018).…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations